Incidence and Evaluation of Incidental Abnormal Bone Marrow Signal on Magnetic Resonance Imaging - Gunjan L. Shah; Aaron S. Rosenberg; Jamie Jarboe; Andreas Klein; Furha Cossor (The Scientific World Journal)
Purpose. The increased use of magnetic resonance imaging (MRI) has resulted in reports of incidental abnormal bone marrow (BM) signal. Our goal was to determine the evaluation of an incidental abnormal BM signal on MRI and the prevalence of a subsequent oncologic diagnosis. Methods. We conducted a retrospective cohort study of patients over age 18 undergoing MRI between May 2005 and October 2010 at Tufts Medical Center (TMC) with follow-up through November 2013. The electronic medical record was queried to determine imaging site, reason for scan, evaluation following radiology report, and final diagnosis. Results. 49,678 MRIs were done with 110 patients meeting inclusion criteria. Twenty two percent underwent some evaluation, most commonly a complete blood count, serum protein electrophoresis, or bone scan. With median follow-up of 41 months, 6% of patients were diagnosed with malignancies including multiple myeloma, non-Hodgkins lymphoma, metastatic non-small cell lung cancer, and metastatic adenocarcinoma. One patient who had not undergone evaluation developed breast cancer 24 months after the MRI. Conclusions. Incidentally noted abnormal or heterogeneous bone marrow signal on MRI was not inconsequential and should prompt further evaluation.